Effects of clodinafop-propargyl on DNA damage of bemocytes in silkworm - YIN Xiao-hui; ZHU Guo-nian; ZHUANG Hui-sheng; WU Hui-ming; LI Shao-nan (浙江大学学报. 农业与生命科学版)
To study and evaluate genotoxicity of clodinafop-propargyl in the silkworm, Bombyx mori, the 2nd, 4th and 5th-instar larvaes of silkworm were fed toxic mulberry leaves treated with different concentrations of 30, 60, 120, 240, 480 mg·L-1, respectively. DNA damage of hemocytes was detected by the comet assay. CASP software was used to analyze the comet pictures. The results show that the percentage of comet, the percentage of head DNA, the percentage of tail DNA, tail length, and tail moment of the five tested groups were significantly different from those of the control group (P<0.01). Compared with control group, the percentage of comet cells of the hemocytes at the 2nd, 4th and 5th-instar of silkworm larvae was 8.3, 5.3 and 6.0 times, the comet tail length of the hemocytes was 10.8, 9.5 and 6.6 times, and the tail moment was 96.7, 86.8 and 22.5 times, respectively, with treatment of the high dose of clodinafop-propargyl. A statistically significant dose-dependent increase in DNA damage was observed in the 2nd, 4th and 5th-instar larvae of silkworm assessed, as evident from the comet-assay parameters, viz., olive tail moment (OTM, arbitrary unit). The clodinafop-propargyl at the different concentration level induced DNA damage of different degree, and the hemocytes isolated from the 2nd-instar larvae was more sensitive to clodinafop-propargyl than that of 4th-instar larvae and 5th~instar larvae. Based on experimental evidence obtained, it was suggested that DNA damage of silkworm, Bombyx mori, may be used as a potential bio-indicator for the genotoxicity assessment of pesticides.